(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-3-21-34 The features of perception of the image of the earth by the heroes of the works of F.M. Dostoevsky, A. Platonov, I.S. Shmelev are considered. It is determined that the world of images created by F.M. Dostoevsky, A.P. Platonov and I.S. Shmelev in artistic texts is built on the basis of semantic oppositions: life – death, day – night, person – nature, one’s own – another’s. One of the obvious oppositions functioning in the texts of the authors under study is the earth–sky opposition. The perception of the image of the earth among the writers under study occurs within the framework of the mythopoetic paradigm, but at the same time each of them creates his own myth. Keywords: mythopoetic model of the world; semantic oppositions; earth; F.M. Dostoevsky; A. Platonov; I.S. Shmelev.